Impact of Economic Integration and Information and Communication Technology on Economic Growth for European Union: Dynamic Panel GMM Approach - Muhammad Bilal, Ahsin; Jerome, Kueh; Muhammad Asraf, Abdullah (Macrothink Institute, 2021)
European Union is the strongest economic union globally and has observed rapid economic growth in the last few decades. This study investigates whether economic integration and information and communication technology (ICT) promotes economic growth in the EU. Additionally, the study examines the role of ICT for economic integration and growth relationship concerning ICT readiness and usage. The study undertook panel data from 2002 to 2019 and employed the Generalized Method of Moments approach to estimate results. The results revealed that economic integration and ICT enhance economic growth. Moreover, enhanced ICT stimulates the impact of economic integration on economic growth. The results also confirmed a more substantial effect of ICT usage on economic growth than ICT readiness.